2022
DOI: 10.3390/nano12122024
|View full text |Cite
|
Sign up to set email alerts
|

Cyto–Genotoxic Effect Causing Potential of Polystyrene Micro-Plastics in Terrestrial Plants

Abstract: The polystyrene micro-plastics (Ps-MPs) is one of the leading pollutants found in both aquatic and terrestrial ecosystems. While most of the studies on the morphology and cyto-toxicity of MPs have been based on aquatic organisms, their effects on terrestrial plants are still scarcely known. The present study was an attempt to measure the effect of different sizes (80, 100, 200, 500, 1000, 2000, 4000, and 8000 nm) and concentrations (100 and 400 mg/L) of Ps-MPs on the root length and chromosomes of root tip cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…In this study, no inhibitory effect on onion root growth was observed after exposure to 147 nm sized PS-MPs. This is in agreement with results obtained on A. cepa roots exposed to PS-MPs of sizes ranging from 80 to 8000 nm [ 32 ], as well as on V. faba [ 22 ] and C. sativus roots [ 33 ] treated with 100 nm sized PS-MPs. On the other hand, a positive effect on root elongation of wheat seedlings was reported upon exposure to 100 nm PS-MPs [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, no inhibitory effect on onion root growth was observed after exposure to 147 nm sized PS-MPs. This is in agreement with results obtained on A. cepa roots exposed to PS-MPs of sizes ranging from 80 to 8000 nm [ 32 ], as well as on V. faba [ 22 ] and C. sativus roots [ 33 ] treated with 100 nm sized PS-MPs. On the other hand, a positive effect on root elongation of wheat seedlings was reported upon exposure to 100 nm PS-MPs [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…Boots et al [ 31 ] observed no changes in germination rate and chlorophyll content in Lolium perenne treated with high-density PE-MPs, while the 48 or 72 h exposure of L. sativum to NPs and MPs failed to reveal significant differences in root growth [ 21 ]. The lack of effect on root growth was also reported for A. cepa [ 32 ], V. faba [ 22 ], and Cucumis sativus [ 33 ] upon exposure to PS-MPs. Moreover, in some studies, even positive, acclimative responses were recorded.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Polystyrene (PS) plastic is widely used as packaging materials such as containers, lids, and trays. It has been reported as a major component of MP found in soil [22]. This study used PSMP (polystyrene microplastic) microspheres with a distribution around 1ߤm mean diameter, within a 0.9ߤm െ 1.1ߤm range, purchased from Bioscientific Pty Ltd (NSW, Australia).…”
Section: Methodsmentioning
confidence: 99%
“…7,69 It has also been shown that these particles are able to induce cytotoxic and genotoxic effects on humans as well as plant species. 70,71 Thus, SUP management initiatives will help to deal with the increasing microplastic pollution (Fig. 1).…”
Section: Positive Implicationsmentioning
confidence: 99%